Presence of Cx43 in extracellular vesicles reduces the cardiotoxicity of the anti-tumour therapeutic approach with doxorubicin - Martins-Marques, Tania (2016)
Extracellular vesicles (EVs) are major conveyors of biological information, mediating local and systemic cell-to-cell communication under physiological and pathological conditions. These endogenous vesicles have been recognized as prominent drug delivery vehicles of several therapeutic cargoes, including doxorubicin (dox), presenting major advantages over the classical approaches. Although dox is one of the most effective anti-tumour agents in the clinical practice, its use is very often hindered by its consequent dramatic cardiotoxicity. Despite significant advances witnessed in the past few years, more comprehensive studies, supporting the therapeutic efficacy of EVs, with decreased side effects, are still scarce. The main objective of this study was to evaluate the role of the gap junction protein connexin43 (Cx43) in mediating the release of EV content into tumour cells. Moreover, we investigated whether Cx43 improves the efficiency of dox-based anti-tumour treatment, with a concomitant decrease of cardiotoxicity. In the present report, we demonstrate that the presence of Cx43 in EVs increases the release of luciferin from EVs into tumour cells in vitro and in vivo. In addition, using cell-based approaches and a subcutaneous mouse tumour model, we show that the anti-tumour effect of dox incorporated into EVs is similar to the administration of the free drug, regardless the presence of Cx43. Strikingly, we demonstrate that the presence of Cx43 in dox-loaded EVs reduces the cardiotoxicity of the drug. Altogether, these results bring new insights into the concrete potential of EVs as therapeutic vehicles and open new avenues toward the development of strategies that help to reduce unwanted side effects.